Professional, Academic, and Institutional Identities of School Administrators with a Ph.D. - İbrahim Hakan Karataş; Mesut Demirbilek (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
The study aims to describe the situation of school administrators (SA) with a Ph.D. and to reveal their professional, organizational, and academic competencies and identity perceptions. In the research, which was conducted in a qualitative framework and phenomenological design, focus group interviews were conducted with eight SAs with a Ph.D. working in private or public schools. The data obtained from the focus group interviews were subjected to content analysis, and common patterns and meanings were revealed within the framework of the purpose. The findings of the study were thematized under the headings of the doctoral education process and its outcomes and professional, academic, institutional/professional competencies and identity of SAs with a Ph.D.. Considering the results obtained within the framework of these themes, it is determined that SAs with a Ph.D. are satisfied with the doctoral education process and gain competence, but experience problems and difficulties in terms of personal rights and institutional and academic dimensions. In addition, it is observed that they experience technical obstacles such as accessing databases and obtaining ethics committee approval in research processes, and their job satisfaction decreases, but their intrinsic motivation is high. In this framework, it has been observed that SAs with a Ph.D. have expectations regarding academic and institutional roles and status, personal rights, and research processes. As a result, it is seen that SAs with a Ph.D. are in search of identity within the Ministry of National Education within the framework of the problems they experience, and their desire to transfer to higher education institutions has increased.